Transition and Obliteration: Jose Garcia Villa in the United States - Chua, Jonathan O (Archīum Ateneo, 2021)
Jose Garcia Villa (1908–1997) was a pioneering Filipino writer in the United States and a key figure in the history of Anglophone Filipino literature. His troubled relations with the literary establishment in the Philippines made him seek acceptance in the US literary world, which, as a colonial subject, he had taken as the summit of validation. As this review of his publication history in the United States shows, however, his foreignness hounded him. While Villa took steps to transition into someone other than a Filipino writer, he could only be accepted in the US literary scene on Orientalist terms – that is, as a subordinate or an imperfect copy of his American originals – and was dispensable.